Pathological Findings and Oxidative Stress Status Associated with Hydatidosis in Dromedary Camels - Salma A. Shoulah; Mohamed M. S. Gaballa; Marawan A. Marawan; Sayed A. Saqr; Abdelhamed Abdelhady; Hayat Ali Alzahrani; Majed H. Wakid; Omar A. Al-Jabr; Abdelfattah Selim (Veterinary Sciences, 2023)
(1) Background: Cystic echinococcosis is a zoonotic helminth disease that causes severe economic losses. The study aimed to assess the prevalence and viability of cystic echinococcosis in examined camels. In addition, assessing the histological, morphological, oxidative, and antioxidant state related to the cystic echinococcosis infection; (2) Methods: The study was performed on 152 slaughtered dromedary camels between March and September 2022 at El-Basatin abattoir in Cairo Governorate, Egypt; (3) Results: The results revealed that the prevalence of hydatidosis was 21.7% in slaughtered camel and the highest infection rate observed in lungs was 87.87%, while it was 9% in livers. Camels’ liver infections were rare, whereas their lung infections were more common. By comparing to non-infected camels, the level of MAD was significantly increased with hydatid cysts infection, while the level of GSH, SOD and CAT was significantly decreased. Histopathological section of camel cyst revealed layered membranes surrounded by a zone of cellular infiltration and an outermost fibrous tissue reaction. In addition, there was evidence of atelectasis, emphysema, hemorrhage, congestion, and fibrosis in the surrounding tissues. Nonetheless, the degeneration and necrosis of hepatocytes and other pathological alterations in liver cyst sections were remarkably comparable to those seen in the lungs. Furthermore, calcification was detected.